Disparities in the prevalence of clinical features between systemic juvenile idiopathic arthritis and adult-onset Still's disease. (25th January 2022) - Ruscitti, Piero; Natoli, Valentina; Consolaro, Alessandro; Caorsi, Roberta; Rosina, Silvia; Giancane, Gabriella; Naddei, Roberta; Di Cola, Ilenia; Di Muzio, Claudia; Berardicurti, Onorina; Iacono, Daniela; Pantano, Ilenia; et al.
Abstract: Objective: To compare clinical features and treatments of patients with systemic JIA (sIJA) and adult-onset Still's disease (AOSD). Methods: The clinical charts of consecutive patients with sJIA by International League of Association of Rheumatology criteria or AOSD by Yamaguchi criteria were reviewed. Patients were seen at a large paediatric rheumatology referral centre or at 10 adult rheumatology academic centres. Data collected included clinical manifestations, inflammation biomarkers, systemic score, macrophage activation syndrome (MAS), parenchymal lung disease, disease course, disability, death and medications administered. Results: A total of 166 patients (median age at diagnosis 5 years) with sJIA and 194 patients with AOSD (median age at diagnosis 41 years) were included. The frequency of fever, rash, arthralgia, abdominal pain, MAS, parenchymal lung disease and increased acute phase reactants and ferritin were comparable between the two cohorts. Patients with sJIA had a higher prevalence of arthritis, whereas patients with AOSD had experienced leucocytosis and extra-articular organ involvement more frequently. Patients with AOSD were given more commonly low-dose corticosteroids, whereas biologic DMARDs were administered first-line more frequently in patients with sJIA. Conclusion: We found remarkable disparities in the prevalence of clinical manifestations between the two illnesses, which may partly depend on their classification by different criteria.